2012
DOI: 10.1016/j.matchar.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Ti–6Al–4V brazed joint strength equal to the base metal by Ti and Zr amorphous filler alloys

Abstract: Microstructural features developed along with mechanical properties in furnace brazingof Ti-6Al-4V alloy using STEMET 1228 (Ti-26.8Zr-13Ni-13.9Cu, wt.%) and STEMET 1406 (Zr-9.7Ti-12.4Ni-11.2Cu, wt.%) amorphous filler alloys. Brazing temperatures employed were 900-950°C for the titanium-based filler and 900-990°C for the zirconium-based filler alloys, respectively. The brazing time durations were 600, 1200 and 1800 s. The brazed joints were evaluated by ultrasonic test, and their microstructures and phase const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…5(a). The formation of the dimples implies plastic deformation in the micro-regions, which is sometimes taken as a positive indication of enhancement of the mechanical properties of the joint, According to these results, the improvement of the Cu/Cu-Ni-Sn-P/Cu brazed joint was achieved because the formation of ductile dimple fracture resulted from the strong bonding and fatigue resistance, and when the brittle fracture formation occurred on the brazing joints, the cracks preferred to propagate at the brittle intermetallic compounds, resulting in an easy propagation of the cracks, which leads to a decrease in the strength and fatigue life of the joints [17]. Fig.…”
Section: Fracture Characteristics Of Brazed Jointsmentioning
confidence: 93%
“…5(a). The formation of the dimples implies plastic deformation in the micro-regions, which is sometimes taken as a positive indication of enhancement of the mechanical properties of the joint, According to these results, the improvement of the Cu/Cu-Ni-Sn-P/Cu brazed joint was achieved because the formation of ductile dimple fracture resulted from the strong bonding and fatigue resistance, and when the brittle fracture formation occurred on the brazing joints, the cracks preferred to propagate at the brittle intermetallic compounds, resulting in an easy propagation of the cracks, which leads to a decrease in the strength and fatigue life of the joints [17]. Fig.…”
Section: Fracture Characteristics Of Brazed Jointsmentioning
confidence: 93%
“…According to the main alloying elements, filler alloys for brazing titanium and its alloys can mainly be classified into five groups: titanium-based [1,14,16,[18][19][20][21], zirconiumbased [16,19,22,23], silver-based [24][25][26][27], aluminum-based [28][29][30][31], and nickel-based [19,32] filler alloys. Attempts of brazing titanium using Al-based filler alloys and other filler systems started over than 60 years ago [33].…”
Section: Introductionmentioning
confidence: 99%
“…e diffusion of some brazing processes, usually in high temperature, may proceed for a relatively long holding time until achieving the microstructure homogenization over all the joint, which is particularly known as diffusion brazing. Matsu et al, Ganjeh et al and Chang et al [16,17,42] investigated the diffusion brazing of several Ti-and Zr-based fillers, which led to specific microstructures and high shear strengths (Table 1). ese processes involve isothermal solidification and homogenization of the joint [43].…”
Section: Introductionmentioning
confidence: 99%
“…There were first report of high glass forming ability (GFA) of Cu-Ti based alloys namely, Cu 47 Ti 34 Zr 11 Ni 8 and Cu 47 Ti 33 Zr 11 Ni 8 Si 1, which can be cast fully amorphous in the rod forms of 4 and 7 mm in diameter [1][2][3][4][5]. Afterwards, much effort were made in order to develop novel Cu-Ti based bulk glassy alloys possessing more GFA and improved mechanical properties [6,7]. However, it has been observed that the metallic glasses have drawbacks which are the lack of ductility shown in tensile experiments and limited plasticity under macroscopic compression.…”
Section: Introductionmentioning
confidence: 99%